Detailed Simulink implementation for induction motor control based on space vector pulse width modulation SVPWM - Taha A. Hussein; Laith A. Mohammed (Institute of Advanced Engineering and Science, 2021)
Space vector pulse width modulation (SVPWM) generates less harmonic distortion in the output voltage or currents, provides more efficient use of supply voltage and better voltage utilization compared with sine pulse width modulation (PWM). In this work, a detailed Simulink implementation for SVPWM for the open loop control of permanent magnet synchronous motor (PMSM) is presented. Results show the output of the blocks that assembles SVPWM besides the PMSM voltages and currents when exposing the motor to different load torques. The technique of SVPWM enables the load to respond to the change in external load torque. This technique also results in lower total harmonic distortion and better utilization of the direct current (DC) supply compared with traditional sinusoidal pulse width modulation sinusoidal pulse width modulation (SPWM).